Preparation method of mattress with negative ion sleep-aiding function
By using nanopowders prepared by using g-C3N4 exciter and hexacyclic tourmaline mixture, combined with the combination technology of aqueous polyurethane and exciter, the problems of insufficient release of negative ion functional products and complex operation in the prior art were solved, and negative ion sleep aid mattress was prepared, achieving efficient negative ion release and improving sleep quality.
Patent Information
- Application Number
- CN202211664016.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-23
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-12-23
AI Technical Summary
In the prior art, the negative ion release amount of negative ion functional products is insufficient, the operation is complex and uncontrollable, and the use of harmful metals is difficult to meet the existing quality of life.
G-C3N4 is used as an exciter to prepare a negative ion release functional exciter through the reaction of urea and water, and is mechanically dried and wet ball milled with a mixture of hexagonal stone and tourmaline to prepare nano powder. It is then compounded with water-based polyurethane and exciter, applied to the surface of the fabric through a dip process to prepare a negative ion sleep aid mattress.
The negative ion release volume of negative ion sleep aid mattress has been increased to 1,000 to 6,000 pieces/cubic centimeter, which has improved air quality and improved sleep quality. The process is simple and low in cost, which is suitable for industrial production.
Smart Images

Figure CN116065402B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the application field of negative ion emitting nano materials, and in particular relates to a method for preparing a mattress with a negative ion sleep-aiding function. Background Art
[0002] In order to maintain the operation of various functions of the body, humans must breathe air, so human health will be directly affected by air pollution. According to some data, there are more than 500 kinds of volatile organic compounds in the indoor environment. The most harmful pollution sources to the human body are formaldehyde, PM2.5, TVOC, benzene, ammonia, etc. Among them, PM2.5 produced by indoor dust, exhaust gas, decoration materials, etc. will increase the incidence of human cardiopulmonary diseases; formaldehyde can cause serious diseases such as nasopharyngeal cancer and laryngeal cancer, and comes from particleboard, density board, etc.
[0003] At present, the concentration of negative ions in the environment has been used as one of the important evaluation indicators of fresh air. After work, people spend half of their time sleeping, but if the air quality of the sleeping environment is not good, it will affect people's sleep quality and even cause harm to the body during sleep. Therefore, more and more researchers are investing in the research of technologies to improve sleep quality.
[0004] At present, the negative ion functional products of the existing technology are used in the textile industry, plastic products, paper products, etc., and the number of negative ions released by these products is about 1200 to 5000 per cubic centimeter. However, at present, the preparation technology of negative ion emitting environmentally friendly fabrics has the disadvantages of complex operation, uncontrollable process, use of harmful metals, etc., which is not conducive to industrial application and the negative ion release is still insufficient to meet the current quality of life requirements. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a mattress with a negative ion sleep-aiding function.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a mattress with negative ion sleep-aiding function, comprising:
[0009] Preparation of negative ion releasing functional activator: g-C3N4 is used as activator, urea is used as raw material, water is used as solvent, stirred at room temperature until colorless and transparent, and dried to obtain g-C3N4 precursor;
[0010] The g-C3N4 precursor is heated to 400-550°C, calcined for 1-4 hours, cooled to room temperature, and then the sample is collected; the temperature is then increased to 500-650°C at the same heating rate, kept at that temperature for 1-4 hours, cooled to room temperature, and the sample is collected to obtain a negative ion release functional stimulator;
[0011] Preparation and modification of negative ion emission functional powder: The mixture of hexacyclic stone and tourmaline is successively subjected to mechanical dry grinding and wet ball milling to obtain negative ion emission functional powder with a particle size of no more than 200 nm; wherein, the wet ball milling uses water as a dispersant, and low molecular weight water-soluble polyethylene glycol or polyvinyl alcohol and polyvinyl pyrrolidone are added;
[0012] Compounding the negative ion emitting functional powder with the adhesive and the activator: Mixing the waterborne polyurethane and the activator in a container, stirring evenly until they are completely dissolved, then adding the negative ion emitting nano powder, stirring evenly, and preparing a negative ion emitting compound solution;
[0013] Preparation of a negative ion sleep-aiding mattress: applying the negative ion emission compound solution to the surface of fabrics through a padding process, and processing the fabrics to prepare a functional mattress.
[0014] As a preferred embodiment of the preparation method of the present invention, the negative ion release functional stimulant is prepared, wherein the concentration of g-C3N4 is 1-19 mol / kg, and the concentration of urea is 1-19 mol / kg.
[0015] As a preferred embodiment of the preparation method of the present invention, the drying process obtains a g-C3N4 precursor, wherein the drying temperature is 100-180°C and the drying time is 8-16h.
[0016] As a preferred embodiment of the preparation method of the present invention, the g-C3N4 precursor is heated to 400-550°C, wherein the heating rate is 5°C / min.
[0017] As a preferred embodiment of the preparation method of the present invention, the mass ratio of hexachlorobenzene to tourmaline is 1:9 to 9:1.
[0018] As a preferred solution of the preparation method of the present invention, the mechanical dry grinding is a process in which a mechanical knife rotates at high speed to obtain an anion powder with a particle size of 0.5 to 10 um.
[0019] As a preferred embodiment of the preparation method of the present invention, the wet ball milling comprises a powder mass concentration of 5-20%, a low molecular weight water-soluble polyethylene glycol or polyvinyl alcohol mass concentration of 0.5-3%, and a polyvinyl pyrrolidone mass concentration of 0.5-3%.
[0020] As a preferred embodiment of the preparation method of the present invention, the negative ion emission compound solution comprises 0.5-5% by mass of waterborne polyurethane, 0.1-1% by mass of activator and 5-20% by mass of negative ion functional powder.
[0021] As a preferred embodiment of the preparation method of the present invention, the preparation of the negative ion sleep-aiding mattress comprises:
[0022] The negative ion emission compound solution is applied to the surface of the fabric through a padding process, and the padding is repeated 1 to 4 times. The fabric after the padding treatment is dried and then subjected to a finishing process to prepare a finished mattress product.
[0023] Another object of the present invention is to overcome the deficiencies in the prior art and provide a mattress with negative ion sleep-aiding function prepared by a preparation method of a mattress with negative ion sleep-aiding function, wherein the negative ion emission amount of the mattress with negative ion sleep-aiding function is 1000 to 6000 per cubic centimeter.
[0024] Beneficial effects of the present invention:
[0025] The g-C3N4 of the present invention has a small specific surface area, is easy to generate photogenerated electrons and promotes the performance of electron transition. When compounded with negative ion releasing functional powder, it can provide an electron transmission channel, improve the point transition efficiency, and thus improve the negative ion generation efficiency.
[0026] The present invention adopts polyethylene glycol or polyvinyl alcohol to modify the surface of the negative ion powder, which can increase the compatibility of the aqueous solution of the negative ion powder. The addition of polyvinyl pyrrolidone can improve its stability and prevent it from aggregating and precipitating. The aqueous polyurethane is used as an adhesive to increase the adhesion of the negative ion powder in the post-finishing drying process, enhance the durability of the negative ion mattress product, improve the air quality of the home environment, improve the sleep quality, relieve fatigue, and thus help sleep.
[0027] The preparation technology of the negative ion functional finishing agent provided by the present invention solves the shortcomings of low emissivity and low efficiency of improving environmental quality of negative ion emitting materials in the prior art. Compared with the traditional preparation method, it has lower cost, convenient operation, controllable particle size of nano powder, high production efficiency, and can be applied to industrial production on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0029] Figure 1 This is the SEM image of the g-C3N4 composite anion nanopowder in the embodiment of the present invention. DETAILED DESCRIPTION
[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0032] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0033] The raw materials in the present invention are all common commercially available products.
[0034] Embodiment 1:
[0035] (1) Using g-C3N4 as an activator, urea as a raw material, and water as a solvent, stirring at room temperature until colorless and transparent, and drying in an oven for 12 hours to obtain a g-C3N4 precursor, wherein the concentration of g-C3N4 is 8 mol / kg and the concentration of urea is 10 mol / kg;
[0036] The g-C3N4 precursor was placed in an alumina crucible, then heated to 400°C at a heating rate of 5°C / min, calcined for 1 h, and after cooling to room temperature, the sample (first calcination product) was collected;
[0037] Then the temperature was raised to 500°C at the same heating rate, kept at that temperature for 1 h, cooled to room temperature and the samples were collected (second calcination product).
[0038] (2) Preparation and modification of negative ion emission functional powder: The negative ion emission functional powder is a mixture of hexachlorobenzene and tourmaline, with a mass ratio of 1:9, obtained by mechanical dry grinding and wet ball milling;
[0039] The first step is mechanical crushing. The larger particles are crushed into smaller particles under the action of high-speed rotation of the mechanical knife. The particle size of the negative ion powder is 2um.
[0040] The second step is to use high-speed wet ball milling, using water as the dispersant, to which a certain proportion of low molecular weight (molecular weight is 2000) water-soluble polyethylene glycol and polyvinyl pyrrolidone (molecular weight is 20000) are added to modify the surface of the anions, increase their compatibility with other systems, and obtain a uniformly dispersed system with a powder diameter of 200nm; wherein, the nanopowder concentration is 5%, the amount of polyethylene glycol added is 0.5%, and the amount of polyvinyl pyrrolidone added is 0.5%.
[0041] (3) Compounding process of negative ion emitting functional powder, adhesive and activator: Mix the water-based polyurethane and activator in a container, stir them evenly on a magnetic stirrer until they are completely dissolved, and then add them to the negative ion emitting nanopowder solution, stir them evenly and set aside for use, wherein the water-based polyurethane added is 0.5%, the activator is 0.1%, and the concentration of negative ion nanopowder is 5%.
[0042] SEM image of g-C3N4 composite anion nanopowder, see Figure 1 .
[0043] (4) Preparing a negative ion sleep-aiding mattress: applying the prepared negative ion emitting composite solution to the surface of fabric through a 1-dip 1-roll process, and processing the fabric into a functional mattress.
[0044] The negative ion mattress has been tested to release 800 negative ions per cubic centimeter.
[0045] Embodiment 2:
[0046] (1) Using g-C3N4 as an activator, urea as a raw material, and water as a solvent, stirring at room temperature until colorless and transparent, and drying in an oven for 12 hours to obtain a g-C3N4 precursor, wherein the concentration of g-C3N4 is 8 mol / kg and the concentration of urea is 10 mol / kg;
[0047] The g-C3N4 precursor was placed in an alumina crucible, then heated to 450°C at a heating rate of 5°C / min, calcined for 1 h, and after cooling to room temperature, the sample (first calcination product) was collected;
[0048] Then the temperature was raised to 500°C at the same heating rate, kept at that temperature for 1 h, cooled to room temperature and the samples were collected (second calcination product).
[0049] (2) Preparation and modification of negative ion emission functional powder: The negative ion emission functional powder is a mixture of hexachlorobenzene and tourmaline, with a mass ratio of 1:9, obtained by mechanical dry grinding and wet ball milling;
[0050] The first step is mechanical crushing. The larger particles are crushed into smaller particles under the action of high-speed rotation of the mechanical knife. The particle size of the negative ion powder is 2um.
[0051] The second step is to use high-speed wet ball milling, using water as the dispersant, to which a certain proportion of low molecular weight (molecular weight is 2000) water-soluble polyethylene glycol and polyvinyl pyrrolidone (molecular weight is 20000) are added to modify the surface of the anions, increase their compatibility with other systems, and obtain a uniformly dispersed system with a powder diameter of 200nm; wherein, the nanopowder concentration is 5%, the amount of polyethylene glycol added is 0.5%, and the amount of polyvinyl pyrrolidone added is 0.5%.
[0052] (3) Compounding process of negative ion emitting functional powder, adhesive and activator: Mix the water-based polyurethane and activator in a container, stir them evenly on a magnetic stirrer until they are completely dissolved, and then add them to the negative ion emitting nanopowder solution, stir them evenly and set aside for use, wherein the water-based polyurethane added is 0.5%, the activator is 0.1%, and the concentration of negative ion nanopowder is 5%.
[0053] (4) Preparing a negative ion sleep-aiding mattress: applying the prepared negative ion emitting composite solution to the surface of fabric through a 1-dip 1-roll process, and processing the fabric into a functional mattress.
[0054] The negative ion mattress has been tested and the negative ion release amount is 820 per cubic centimeter.
[0055] Embodiment 3:
[0056] (1) Using g-C3N4 as an activator, urea as a raw material, and water as a solvent, stirring at room temperature until colorless and transparent, and drying in an oven for 12 hours to obtain a g-C3N4 precursor, wherein the concentration of g-C3N4 is 8 mol / kg and the concentration of urea is 10 mol / kg;
[0057] The g-C3N4 precursor was placed in an alumina crucible, then heated to 500°C at a heating rate of 5°C / min, calcined for 1 h, and after cooling to room temperature, the sample (first calcination product) was collected;
[0058] Then the temperature was raised to 550°C at the same heating rate, kept at that temperature for 1 h, cooled to room temperature and the samples were collected (second calcination product).
[0059] (2) Preparation and modification of negative ion emission functional powder: The negative ion emission functional powder is a mixture of hexachlorobenzene and tourmaline, with a mass ratio of 1:9, obtained by mechanical dry grinding and wet ball milling;
[0060] The first step is mechanical crushing. The larger particles are crushed into smaller particles under the action of high-speed rotation of the mechanical knife. The particle size of the negative ion powder is 2um.
[0061] The second step is to use high-speed wet ball milling, using water as the dispersant, to which a certain proportion of low molecular weight (molecular weight is 2000) water-soluble polyethylene glycol and polyvinyl pyrrolidone (molecular weight is 20000) are added to modify the surface of the anions, increase their compatibility with other systems, and obtain a uniformly dispersed system with a powder diameter of 200nm; wherein, the nanopowder concentration is 5%, the amount of polyethylene glycol added is 0.5%, and the amount of polyvinyl pyrrolidone added is 0.5%.
[0062] (3) Compounding process of negative ion emitting functional powder, adhesive and activator: Mix the water-based polyurethane and activator in a container, stir them evenly on a magnetic stirrer until they are completely dissolved, and then add them to the negative ion emitting nanopowder solution, stir them evenly and set aside for use, wherein the water-based polyurethane added is 0.5%, the activator is 0.1%, and the concentration of negative ion nanopowder is 5%.
[0063] (4) Preparing a negative ion sleep-aiding mattress: applying the prepared negative ion emitting composite solution to the surface of fabric through a 1-dip 1-roll process, and processing the fabric into a functional mattress.
[0064] The negative ion mattress has been tested and the negative ion release amount is 880 per cubic centimeter.
[0065] Embodiment 4:
[0066] (1) Using g-C3N4 as an activator, urea as a raw material, and water as a solvent, stirring at room temperature until colorless and transparent, and drying in an oven for 12 hours to obtain a g-C3N4 precursor, wherein the concentration of g-C3N4 is 8 mol / kg and the concentration of urea is 10 mol / kg;
[0067] The g-C3N4 precursor was placed in an alumina crucible, then heated to 550°C at a heating rate of 5°C / min, calcined for 1 h, and after cooling to room temperature, the sample (first calcination product) was collected;
[0068] Then the temperature was raised to 600 °C at the same heating rate, kept at that temperature for 1 h, cooled to room temperature and the samples were collected (second calcination product).
[0069] (2) Preparation and modification of negative ion emission functional powder: The negative ion emission functional powder is a mixture of hexachlorobenzene and tourmaline, with a mass ratio of 1:9, obtained by mechanical dry grinding and wet ball milling;
[0070] The first step is mechanical crushing. The larger particles are crushed into smaller particles under the action of high-speed rotation of the mechanical knife. The particle size of the negative ion powder is 2um.
[0071] The second step is to use high-speed wet ball milling, using water as the dispersant, to which a certain proportion of low molecular weight (molecular weight is 2000) water-soluble polyethylene glycol and polyvinyl pyrrolidone (molecular weight is 20000) are added to modify the surface of the anions, increase their compatibility with other systems, and obtain a uniformly dispersed system with a powder diameter of 200nm; wherein, the nanopowder concentration is 5%, the amount of polyethylene glycol added is 0.5%, and the amount of polyvinyl pyrrolidone added is 0.5%.
[0072] (3) Compounding process of negative ion emitting functional powder, adhesive and activator: Mix the water-based polyurethane and activator in a container, stir them evenly on a magnetic stirrer until they are completely dissolved, and then add them to the negative ion emitting nanopowder solution, stir them evenly and set aside for use, wherein the water-based polyurethane added is 0.5%, the activator is 0.1%, and the concentration of negative ion nanopowder is 5%.
[0073] (4) Preparing a negative ion sleep-aiding mattress: applying the prepared negative ion emitting composite solution to the surface of fabric through a 1-dip 1-roll process, and processing the fabric into a functional mattress.
[0074] The negative ion mattress has been tested and the negative ion release amount is 860 per cubic centimeter.
[0075] The data show that the optimal conditions for preparing the activator are primary calcination at 500°C and secondary calcination at 550°C.
[0076] Embodiment 5:
[0077] (1) Using g-C3N4 as an activator, urea as a raw material, and water as a solvent, stirring at room temperature until colorless and transparent, and drying in an oven for 12 hours to obtain a g-C3N4 precursor, wherein the concentration of g-C3N4 is 8 mol / kg and the concentration of urea is 10 mol / kg;
[0078] The g-C3N4 precursor was placed in an alumina crucible, then heated to 500°C at a heating rate of 5°C / min, calcined for 1 h, and after cooling to room temperature, the sample (first calcination product) was collected;
[0079] Then the temperature was raised to 550°C at the same heating rate, kept at that temperature for 1 h, cooled to room temperature and the samples were collected (second calcination product).
[0080] (2) Preparation and modification of negative ion emission functional powder: The negative ion emission functional powder is a mixture of hexachlorobenzene and tourmaline, with a mass ratio of 1:4, obtained by mechanical dry grinding and wet ball milling;
[0081] The first step is mechanical crushing. The larger particles are crushed into smaller particles under the action of high-speed rotation of the mechanical knife. The particle size of the negative ion powder is 2um.
[0082] The second step is to use high-speed wet ball milling, using water as the dispersant, to which a certain proportion of low molecular weight (molecular weight is 2000) water-soluble polyethylene glycol and polyvinyl pyrrolidone (molecular weight is 20000) are added to modify the surface of the anions, increase their compatibility with other systems, and obtain a uniformly dispersed system with a powder diameter of 200nm; wherein, the nanopowder concentration is 5%, the amount of polyethylene glycol added is 0.5%, and the amount of polyvinyl pyrrolidone added is 0.5%.
[0083] (3) Compounding process of negative ion emitting functional powder, adhesive and activator: Mix the water-based polyurethane and activator in a container, stir them evenly on a magnetic stirrer until they are completely dissolved, and then add them to the negative ion emitting nanopowder solution, stir them evenly and set aside for use, wherein the water-based polyurethane added is 0.5%, the activator is 0.1%, and the concentration of negative ion nanopowder is 5%.
[0084] (4) Preparing a negative ion sleep-aiding mattress: applying the prepared negative ion emitting composite solution to the surface of fabric through a 1-dip 1-roll process, and processing the fabric into a functional mattress.
[0085] The negative ion mattress has been tested and the negative ion release amount is 930 per cubic centimeter.
[0086] Embodiment 6:
[0087] (1) Using g-C3N4 as an activator, urea as a raw material, and water as a solvent, stirring at room temperature until colorless and transparent, and drying in an oven for 12 hours to obtain a g-C3N4 precursor, wherein the concentration of g-C3N4 is 8 mol / kg and the concentration of urea is 10 mol / kg;
[0088] The g-C3N4 precursor was placed in an alumina crucible, then heated to 500°C at a heating rate of 5°C / min, calcined for 1 h, and after cooling to room temperature, the sample (first calcination product) was collected;
[0089] Then the temperature was raised to 550°C at the same heating rate, kept at that temperature for 1 h, cooled to room temperature and the samples were collected (second calcination product).
[0090] (2) Preparation and modification of negative ion emission functional powder: The negative ion emission functional powder is a mixture of hexachlorobenzene and tourmaline, with a mass ratio of 1:2, obtained by mechanical dry grinding and wet ball milling;
[0091] The first step is mechanical crushing. The larger particles are crushed into smaller particles under the action of high-speed rotation of the mechanical knife. The particle size of the negative ion powder is 2um.
[0092] The second step is to use high-speed wet ball milling, using water as the dispersant, to which a certain proportion of low molecular weight (molecular weight is 2000) water-soluble polyethylene glycol and polyvinyl pyrrolidone (molecular weight is 20000) are added to modify the surface of the anions, increase their compatibility with other systems, and obtain a uniformly dispersed system with a powder diameter of 200nm; wherein, the nanopowder concentration is 5%, the amount of polyethylene glycol added is 0.5%, and the amount of polyvinyl pyrrolidone added is 0.5%.
[0093] (3) Compounding process of negative ion emitting functional powder, adhesive and activator: Mix the water-based polyurethane and activator in a container, stir them evenly on a magnetic stirrer until they are completely dissolved, and then add them to the negative ion emitting nanopowder solution, stir them evenly and set aside for use, wherein the water-based polyurethane added is 0.5%, the activator is 0.1%, and the concentration of negative ion nanopowder is 5%.
[0094] (4) Preparing a negative ion sleep-aiding mattress: applying the prepared negative ion emitting composite solution to the surface of fabric through a 1-dip 1-roll process, and processing the fabric into a functional mattress.
[0095] The negative ion mattress has been tested and the negative ion release amount is 980 per cubic centimeter.
[0096] Embodiment 7:
[0097] (1) Using g-C3N4 as an activator, urea as a raw material, and water as a solvent, stirring at room temperature until colorless and transparent, and drying in an oven for 12 hours to obtain a g-C3N4 precursor, wherein the concentration of g-C3N4 is 8 mol / kg and the concentration of urea is 10 mol / kg;
[0098] The g-C3N4 precursor was placed in an alumina crucible, then heated to 500°C at a heating rate of 5°C / min, calcined for 1 h, and after cooling to room temperature, the sample (first calcination product) was collected;
[0099] Then the temperature was raised to 550°C at the same heating rate, kept at that temperature for 1 h, cooled to room temperature and the samples were collected (second calcination product).
[0100] (2) Preparation and modification of negative ion emission functional powder: The negative ion emission functional powder is a mixture of hexachlorite and tourmaline, with a mass ratio of 1:1, obtained by mechanical dry grinding and wet ball milling;
[0101] The first step is mechanical crushing. The larger particles are crushed into smaller particles under the action of high-speed rotation of the mechanical knife. The particle size of the negative ion powder is 2um.
[0102] The second step is to use high-speed wet ball milling, using water as the dispersant, to which a certain proportion of low molecular weight (molecular weight is 2000) water-soluble polyethylene glycol and polyvinyl pyrrolidone (molecular weight is 20000) are added to modify the surface of the anions, increase their compatibility with other systems, and obtain a uniformly dispersed system with a powder diameter of 200nm; wherein, the nanopowder concentration is 5%, the amount of polyethylene glycol added is 0.5%, and the amount of polyvinyl pyrrolidone added is 0.5%.
[0103] (3) Compounding process of negative ion emitting functional powder, adhesive and activator: Mix the water-based polyurethane and activator in a container, stir them evenly on a magnetic stirrer until they are completely dissolved, and then add them to the negative ion emitting nanopowder solution, stir them evenly and set aside for use, wherein the water-based polyurethane added is 0.5%, the activator is 0.1%, and the concentration of negative ion nanopowder is 5%.
[0104] (4) Preparing a negative ion sleep-aiding mattress: applying the prepared negative ion emitting composite solution to the surface of fabric through a 1-dip 1-roll process, and processing the fabric into a functional mattress.
[0105] The negative ion mattress has been tested and the negative ion release amount is 960 per cubic centimeter.
[0106] Continue to increase the tourmaline content, and the amount of negative ions released will decrease instead. Therefore, the optimal ratio of hexachlorobenzene to tourmaline is 1:2.
[0107] Embodiment 8:
[0108] (1) Using g-C3N4 as an activator, urea as a raw material, and water as a solvent, stirring at room temperature until colorless and transparent, and drying in an oven for 12 hours to obtain a g-C3N4 precursor, wherein the concentration of g-C3N4 is 8 mol / kg and the concentration of urea is 10 mol / kg;
[0109] The g-C3N4 precursor was placed in an alumina crucible, then heated to 500°C at a heating rate of 5°C / min, calcined for 1 h, and after cooling to room temperature, the sample (first calcination product) was collected;
[0110] Then the temperature was raised to 550°C at the same heating rate, kept at that temperature for 1 h, cooled to room temperature and the samples were collected (second calcination product).
[0111] (2) Preparation and modification of negative ion emission functional powder: The negative ion emission functional powder is a mixture of hexachlorobenzene and tourmaline, with a mass ratio of 1:2, obtained by mechanical dry grinding and wet ball milling;
[0112] The first step is mechanical crushing. The larger particles are crushed into smaller particles under the action of high-speed rotation of the mechanical knife. The particle size of the negative ion powder is 2um.
[0113] The second step is to use high-speed wet ball milling, using water as the dispersant, to which a certain proportion of low molecular weight (molecular weight is 2000) water-soluble polyethylene glycol and polyvinyl pyrrolidone (molecular weight is 20000) are added to modify the surface of the anions, increase their compatibility with other systems, and obtain a uniformly dispersed system with a powder diameter of 200nm; wherein the nanopowder concentration is 10%, the polyethylene glycol addition amount is 1%, and the polyvinyl pyrrolidone addition amount is 1%.
[0114] (3) Compounding process of negative ion emitting functional powder, adhesive and activator: Mix the water-based polyurethane and activator in a container, stir them evenly on a magnetic stirrer until they are completely dissolved, and then add them to the negative ion emitting nanopowder solution, stir them evenly and set aside for use, wherein the water-based polyurethane added is 1%, the activator is 0.2%, and the concentration of negative ion nanopowder is 10%.
[0115] (4) Preparing a negative ion sleep-aiding mattress: applying the prepared negative ion emitting composite solution to the surface of fabric through a 1-dip 1-roll process, and processing the fabric into a functional mattress.
[0116] After testing, the negative ion mattress released 1580 negative ions per cubic centimeter.
[0117] Embodiment 9:
[0118] (1) Using g-C3N4 as an activator, urea as a raw material, and water as a solvent, stirring at room temperature until colorless and transparent, and drying in an oven for 12 hours to obtain a g-C3N4 precursor, wherein the concentration of g-C3N4 is 8 mol / kg and the concentration of urea is 10 mol / kg;
[0119] The g-C3N4 precursor was placed in an alumina crucible, then heated to 500°C at a heating rate of 5°C / min, calcined for 1 h, and after cooling to room temperature, the sample (first calcination product) was collected;
[0120] Then the temperature was raised to 550°C at the same heating rate, kept at that temperature for 1 h, cooled to room temperature and the samples were collected (second calcination product).
[0121] (2) Preparation and modification of negative ion emission functional powder: The negative ion emission functional powder is a mixture of hexachlorobenzene and tourmaline, with a mass ratio of 1:2, obtained by mechanical dry grinding and wet ball milling;
[0122] The first step is mechanical crushing. The larger particles are crushed into smaller particles under the action of high-speed rotation of the mechanical knife. The particle size of the negative ion powder is 2um.
[0123] The second step is to use high-speed wet ball milling, using water as the dispersant, to which a certain proportion of low molecular weight (molecular weight is 2000) water-soluble polyethylene glycol and polyvinyl pyrrolidone (molecular weight is 20000) are added to modify the surface of the anions, increase their compatibility with other systems, and obtain a uniformly dispersed system with a powder diameter of 200nm; wherein the nanopowder concentration is 15%, the amount of polyethylene glycol added is 1.5%, and the amount of polyvinyl pyrrolidone added is 1.5%.
[0124] (3) Compounding process of negative ion emitting functional powder, adhesive and activator: Mix the water-based polyurethane and activator in a container, stir them evenly on a magnetic stirrer until they are completely dissolved, and then add them to the negative ion emitting nanopowder solution, stir them evenly and set aside for use. The water-based polyurethane added is 1.5%, the activator is 0.3%, and the concentration of negative ion nanopowder is 15%.
[0125] (4) Preparing a negative ion sleep-aiding mattress: applying the prepared negative ion emitting composite solution to the surface of fabric through a 1-dip 1-roll process, and processing the fabric into a functional mattress.
[0126] The negative ion mattress has been tested and the negative ion release amount is 2150 per cubic centimeter.
[0127] Embodiment 10:
[0128] (1) Using g-C3N4 as an activator, urea as a raw material, and water as a solvent, stirring at room temperature until colorless and transparent, and drying in an oven for 12 hours to obtain a g-C3N4 precursor, wherein the concentration of g-C3N4 is 8 mol / kg and the concentration of urea is 10 mol / kg;
[0129] The g-C3N4 precursor was placed in an alumina crucible, then heated to 500°C at a heating rate of 5°C / min, calcined for 1 h, and after cooling to room temperature, the sample (first calcination product) was collected;
[0130] Then the temperature was raised to 550°C at the same heating rate, kept at that temperature for 1 h, cooled to room temperature and the samples were collected (second calcination product).
[0131] (2) Preparation and modification of negative ion emission functional powder: The negative ion emission functional powder is a mixture of hexachlorobenzene and tourmaline, with a mass ratio of 1:2, obtained by mechanical dry grinding and wet ball milling;
[0132] The first step is mechanical crushing. The larger particles are crushed into smaller particles under the action of high-speed rotation of the mechanical knife. The particle size of the negative ion powder is 2um.
[0133] The second step is to use high-speed wet ball milling, using water as the dispersant, to which a certain proportion of low molecular weight (molecular weight is 2000) water-soluble polyethylene glycol and polyvinyl pyrrolidone (molecular weight is 20000) are added to modify the surface of the anions, increase their compatibility with other systems, and obtain a uniformly dispersed system with a powder diameter of 200nm; wherein the nanopowder concentration is 20%, the amount of polyethylene glycol added is 2%, and the amount of polyvinyl pyrrolidone added is 2%.
[0134] (3) Compounding process of negative ion emitting functional powder, adhesive and activator: Mix the water-based polyurethane and activator in a container, stir them evenly on a magnetic stirrer until they are completely dissolved, and then add them to the negative ion emitting nanopowder solution, stir them evenly and set aside for use, wherein the water-based polyurethane added is 2%, the activator is 0.4%, and the concentration of negative ion nanopowder is 20%.
[0135] (4) Preparing a negative ion sleep-aiding mattress: applying the prepared negative ion emitting composite solution to the surface of fabric through a 1-dip 1-roll process, and processing the fabric into a functional mattress.
[0136] After testing, the negative ion mattress released 2230 negative ions per cubic centimeter.
[0137] Although the concentration of negative ion nanopowder is increased at this time, the amount of negative ion emission does not increase much. Therefore, the optimal process conditions are: nanopowder concentration is 15%, polyethylene glycol addition is 1.5%, polyvinyl pyrrolidone addition is 1.5%; water-based polyurethane addition is 1.5%, and activator is 0.3%.
[0138] Embodiment 11:
[0139] (1) Using g-C3N4 as an activator, urea as a raw material, and water as a solvent, stirring at room temperature until colorless and transparent, and drying in an oven for 12 hours to obtain a g-C3N4 precursor, wherein the concentration of g-C3N4 is 8 mol / kg and the concentration of urea is 10 mol / kg;
[0140] The g-C3N4 precursor was placed in an alumina crucible, then heated to 500°C at a heating rate of 5°C / min, calcined for 1 h, and after cooling to room temperature, the sample (first calcination product) was collected;
[0141] Then the temperature was raised to 550°C at the same heating rate, kept at that temperature for 1 h, cooled to room temperature and the samples were collected (second calcination product).
[0142] (2) Preparation and modification of negative ion emission functional powder: The negative ion emission functional powder is a mixture of hexachlorobenzene and tourmaline, with a mass ratio of 1:2, obtained by mechanical dry grinding and wet ball milling;
[0143] The first step is mechanical crushing. The larger particles are crushed into smaller particles under the action of high-speed rotation of the mechanical knife. The particle size of the negative ion powder is 2um.
[0144] The second step is to use high-speed wet ball milling, using water as the dispersant, to which a certain proportion of low molecular weight (molecular weight is 2000) water-soluble polyethylene glycol and polyvinyl pyrrolidone (molecular weight is 20000) are added to modify the surface of the anions, increase their compatibility with other systems, and obtain a uniformly dispersed system with a powder diameter of 200nm; wherein the nanopowder concentration is 15%, the amount of polyethylene glycol added is 1.5%, and the amount of polyvinyl pyrrolidone added is 1.5%.
[0145] (3) Compounding process of negative ion emitting functional powder, adhesive and activator: Mix the water-based polyurethane and activator in a container, stir them evenly on a magnetic stirrer until they are completely dissolved, and then add them to the negative ion emitting nanopowder solution, stir them evenly and set aside for use. The water-based polyurethane added is 1.5%, the activator is 0.3%, and the concentration of negative ion nanopowder is 15%.
[0146] (4) Preparation of a negative ion sleep-aiding mattress: The prepared negative ion emission compound solution is applied to the surface of the fabric by a 2-dip 2-roll process, and the fabric is processed into a functional mattress. The negative ion mattress is tested to release 3850 negative ions per cubic centimeter.
[0147] Embodiment 12:
[0148] (1) Using g-C3N4 as an activator, urea as a raw material, and water as a solvent, stirring at room temperature until colorless and transparent, and drying in an oven for 12 hours to obtain a g-C3N4 precursor, wherein the concentration of g-C3N4 is 8 mol / kg and the concentration of urea is 10 mol / kg;
[0149] The g-C3N4 precursor was placed in an alumina crucible, then heated to 500°C at a heating rate of 5°C / min, calcined for 1 h, and after cooling to room temperature, the sample (first calcination product) was collected;
[0150] Then the temperature was raised to 550°C at the same heating rate, kept at that temperature for 1 h, cooled to room temperature and the samples were collected (second calcination product).
[0151] (2) Preparation and modification of negative ion emission functional powder: The negative ion emission functional powder is a mixture of hexachlorobenzene and tourmaline, with a mass ratio of 1:2, obtained by mechanical dry grinding and wet ball milling;
[0152] The first step is mechanical crushing. The larger particles are crushed into smaller particles under the action of high-speed rotation of the mechanical knife. The particle size of the negative ion powder is 2um.
[0153] The second step is to use high-speed wet ball milling, using water as the dispersant, to which a certain proportion of low molecular weight (molecular weight is 2000) water-soluble polyethylene glycol and polyvinyl pyrrolidone (molecular weight is 20000) are added to modify the surface of the anions, increase their compatibility with other systems, and obtain a uniformly dispersed system with a powder diameter of 200nm; wherein the nanopowder concentration is 15%, the amount of polyethylene glycol added is 1.5%, and the amount of polyvinyl pyrrolidone added is 1.5%.
[0154] (3) Compounding process of negative ion emitting functional powder, adhesive and activator: Mix the water-based polyurethane and activator in a container, stir them evenly on a magnetic stirrer until they are completely dissolved, and then add them to the negative ion emitting nanopowder solution, stir them evenly and set aside for use. The water-based polyurethane added is 1.5%, the activator is 0.3%, and the concentration of negative ion nanopowder is 15%.
[0155] (4) Preparing a negative ion sleep-aiding mattress: applying the prepared negative ion emitting composite solution to the surface of fabric through a 3-dip 3-roll process, and processing the fabric into a functional mattress.
[0156] The negative ion mattress has been tested and the negative ion release amount is 4050 per cubic centimeter.
[0157] Although the amount of anion released increases with increasing the number of padding times, the increase in padding processes also increases production costs, and the increase in anion release is not obvious at this time. Therefore, the optimal padding process is 2 dips and 2 pads.
[0158] Comparative Example 1
[0159] (1) Using g-C3N4 as an activator, urea as a raw material, and water as a solvent, stirring at room temperature until colorless and transparent, and drying in an oven for 12 hours to obtain a g-C3N4 precursor, wherein the concentration of g-C3N4 is 8 mol / kg and the concentration of urea is 10 mol / kg;
[0160] The g-C3N4 precursor was placed in an alumina crucible, then heated to 500°C at a heating rate of 5°C / min, calcined for 1 h, and after cooling to room temperature, the sample (first calcination product) was collected;
[0161] Then the temperature was raised to 550°C at the same heating rate, kept at that temperature for 1 h, cooled to room temperature and the samples were collected (second calcination product).
[0162] (2) Preparation and modification of negative ion emission functional powder: The negative ion emission functional powder is a mixture of hexachlorobenzene and tourmaline, with a mass ratio of 1:2, obtained by mechanical dry grinding and wet ball milling;
[0163] The first step is mechanical crushing. The larger particles are crushed into smaller particles under the action of high-speed rotation of the mechanical knife. The particle size of the negative ion powder is 2um.
[0164] The second step is to use high-speed wet ball milling, using water as the dispersant, to which water-soluble polyethylene glycol (molecular weight of 2000) is added to obtain a uniform dispersion system with a powder diameter of 200nm; wherein, the nano powder concentration is 15% and the amount of polyethylene glycol added is 3%.
[0165] (3) Compounding process of negative ion emitting functional powder, adhesive and activator: Mix the water-based polyurethane and activator in a container, stir them evenly on a magnetic stirrer until they are completely dissolved, and then add them to the negative ion emitting nanopowder solution, stir them evenly and set aside for use. The water-based polyurethane added is 1.5%, the activator is 0.3%, and the concentration of negative ion nanopowder is 15%.
[0166] (4) Preparing a negative ion sleep-aiding mattress: applying the prepared negative ion emitting composite solution to the surface of fabric through a 2-dip 2-roll process, and processing the fabric into a functional mattress.
[0167] After testing, the negative ion mattress released 3710 negative ions per cubic centimeter.
[0168] Comparative Example 2
[0169] (1) Using g-C3N4 as an activator, urea as a raw material, and water as a solvent, stirring at room temperature until colorless and transparent, and drying in an oven for 12 hours to obtain a g-C3N4 precursor, wherein the concentration of g-C3N4 is 8 mol / kg and the concentration of urea is 10 mol / kg;
[0170] The g-C3N4 precursor was placed in an alumina crucible, then heated to 500°C at a heating rate of 5°C / min, calcined for 1 h, and after cooling to room temperature, the sample (first calcination product) was collected;
[0171] Then the temperature was raised to 550°C at the same heating rate, kept at that temperature for 1 h, cooled to room temperature and the samples were collected (second calcination product).
[0172] (2) Preparation and modification of negative ion emission functional powder: The negative ion emission functional powder is a mixture of hexachlorobenzene and tourmaline, with a mass ratio of 1:2, obtained by mechanical dry grinding and wet ball milling;
[0173] The first step is mechanical crushing. The larger particles are crushed into smaller particles under the action of high-speed rotation of the mechanical knife. The particle size of the negative ion powder is 2um.
[0174] The second step is to obtain a dispersed system by high-speed wet ball milling, using water as the dispersant, to which polyvinyl pyrrolidone (molecular weight of 20,000) is added, and the powder diameter is 200 nm; wherein the nano powder concentration is 15% and the amount of polyvinyl pyrrolidone added is 3%.
[0175] (3) Compounding process of negative ion emitting functional powder, adhesive and activator: Mix the water-based polyurethane and activator in a container, stir them evenly on a magnetic stirrer until they are completely dissolved, and then add them to the negative ion emitting nanopowder solution, stir them evenly and set aside for use. The water-based polyurethane added is 1.5%, the activator is 0.3%, and the concentration of negative ion nanopowder is 15%.
[0176] (4) Preparing a negative ion sleep-aiding mattress: applying the prepared negative ion emitting composite solution to the surface of fabric through a 2-dip 2-roll process, and processing the fabric into a functional mattress.
[0177] After testing, the negative ion mattress released 3680 negative ions per cubic centimeter.
[0178] Comparative Example 3
[0179] (1) Using g-C3N4 as an activator, urea as a raw material, and water as a solvent, stirring at room temperature until colorless and transparent, and drying in an oven for 12 hours to obtain a g-C3N4 precursor, wherein the concentration of g-C3N4 is 8 mol / kg and the concentration of urea is 10 mol / kg;
[0180] The g-C3N4 precursor was placed in an alumina crucible, then heated to 500°C at a heating rate of 5°C / min, calcined for 2h, and then cooled to room temperature before collecting the sample.
[0181] (2) Preparation and modification of negative ion emission functional powder: The negative ion emission functional powder is a mixture of hexachlorobenzene and tourmaline, with a mass ratio of 1:2, obtained by mechanical dry grinding and wet ball milling;
[0182] The first step is mechanical crushing. The larger particles are crushed into smaller particles under the action of high-speed rotation of the mechanical knife. The particle size of the negative ion powder is 2um.
[0183] The second step is to use high-speed wet ball milling, using water as the dispersant, to which a certain proportion of low molecular weight (molecular weight is 2000) water-soluble polyethylene glycol and polyvinyl pyrrolidone (molecular weight is 20000) are added to modify the surface of the anions, increase their compatibility with other systems, and obtain a uniformly dispersed system with a powder diameter of 200nm; wherein the nanopowder concentration is 15%, the amount of polyethylene glycol added is 1.5%, and the amount of polyvinyl pyrrolidone added is 1.5%.
[0184] (3) Compounding process of negative ion emitting functional powder, adhesive and activator: Mix the water-based polyurethane and activator in a container, stir them evenly on a magnetic stirrer until they are completely dissolved, and then add them to the negative ion emitting nanopowder solution, stir them evenly and set aside for use. The water-based polyurethane added is 1.5%, the activator is 0.3%, and the concentration of negative ion nanopowder is 15%.
[0185] (4) Preparation of a negative ion sleep-aiding mattress: The prepared negative ion emission compound solution is applied to the surface of the fabric by a 2-dip 2-roll process, and the fabric is processed into a functional mattress. The negative ion mattress is tested to release 3120 negative ions per cubic centimeter.
[0186] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a mattress with negative ion sleep-aiding function, characterized in that: include, Preparation of negative ion releasing functional activator: g-C3N4 is used as activator, urea is used as raw material, water is used as solvent, stirred at room temperature until colorless and transparent, and dried to obtain g-C3N4 precursor; The g-C3N4 precursor is heated to 400-550°C, calcined for 1-4 hours, cooled to room temperature, and then the sample is collected; the temperature is then increased to 500-650°C at the same heating rate, kept at that temperature for 1-4 hours, cooled to room temperature, and the sample is collected to obtain a negative ion release functional stimulator; Preparation and modification of negative ion emission functional powder: The mixture of hexacyclosite and tourmaline is successively subjected to mechanical dry grinding and wet ball milling to obtain negative ion emission functional powder with a particle size of no more than 200 nm; wherein, in the wet ball milling, the dispersant used is water, and water-soluble polyethylene glycol and polyvinyl pyrrolidone are added, wherein the molecular weight of polyethylene glycol is 2000, and the molecular weight of polyvinyl pyrrolidone is 20000; Compounding the negative ion emitting functional powder with the adhesive and the activator: Mixing the waterborne polyurethane and the activator in a container, stirring evenly until they are completely dissolved, then adding the negative ion emitting nano powder, stirring evenly, and preparing a negative ion emitting compound solution; Preparation of a negative ion sleep-aiding mattress: applying the negative ion emission compound solution to the surface of fabrics through a padding process, and processing the fabrics to prepare a functional mattress.
2. The preparation method according to claim 1, characterized in that: The negative ion releasing functional stimulant is prepared, wherein the concentration of g-C3N4 is 1-19 mol / kg, and the concentration of urea is 1-19 mol / kg.
3. The preparation method according to claim 1, characterized in that: The drying process obtains a g-C3N4 precursor, wherein the drying temperature is 100-180°C and the drying time is 8-16h.
4. The preparation method according to claim 1, characterized in that: The g-C3N4 precursor is heated to 400-550°C, wherein the heating rate is 5°C / min.
5. The preparation method according to claim 1, characterized in that: The mixed mass ratio of hexalobite and tourmaline is 1:9~9:
1.
6. The preparation method according to claim 1, characterized in that: The mechanical dry grinding is that the particle size of the negative ion powder is 0.5-10um under the high-speed rotation of the mechanical knife.
7. The preparation method according to claim 1 or 6, characterized in that: In the wet ball milling, the mass concentration of the powder is 5-20%, the mass concentration of the water-soluble polyethylene glycol is 0.5-3%, and the mass concentration of the polyvinyl pyrrolidone is 0.5~3%.
8. The preparation method according to claim 1, characterized in that: The negative ion emission composite solution comprises 0.5-5% by mass of waterborne polyurethane, 0.1-1% by mass of activator and 5-20% by mass of negative ion functional powder.
9. The preparation method according to claim 1, characterized in that: The method for preparing a negative ion sleeping-aiding mattress comprises: The negative ion emission compound solution is applied to the surface of the fabric through a padding process, and the padding is repeated 1 to 4 times. The fabric after the padding treatment is dried and then subjected to a finishing process to prepare a finished mattress product.
10. A mattress with negative ion sleep-aiding function prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The negative ion emission amount of the negative ion sleeping-aiding mattress is 1000-6000 per cubic centimeter.
Citation Information
Patent Citations
Preparation method for C3N4-excited natural ore negative-ion-emitting nanocomposite and product thereof
CN109207124A
Preparation method of nano coating capable of releasing negative oxygen ions and far infrared rays
CN114316800A